Assessing Emotion Regulation Strategies in Chile: A Spanish Language Adaptation of the German SSKJ 3-8 Scales - Weis, Mirjam; Heine, Jörg-Henrik (Frontiers in Psychology, 2020)
The aim of the present study is the psychometric review of a Spanish language version of the German Stress and Coping Questionnaire for Children and Adolescents (SSKJ 3-8). The SSKJ 3-8 assesses emotion regulation strategies by asking children to indicate how often they use five different emotion regulation strategies in response to a social and an academic stress situation. The Spanish language adaptation of the inventory was developed for a cross-cultural study with Chilean and German fourth-graders. The sample includes 76 German and 169 Chilean fourth graders. The SSKJ 3-8 was first translated into Spanish by a bilingual translator, then back-translated by a German native speaker, and finally adapted for the cultural context in Chile. To analyze the psychometric comparability, the measurement invariance was examined within the framework of the Item Response Theory (IRT) with the R package pairwise. The results show that the new developed Spanish language adaptation of the SSKJ 3-8 is comparable to the German version in terms of psychometric measurement characteristics. Only few items show deviations with regard to strong measurement invariance. We conclude that the Spanish language adaptation of the SSKJ 3-8 is a reliable instrument to assess emotion regulation strategies in Chile.